Biodegradable polycaprolactone-based composites reinforced with ramie and borassus fibres. (1st May 2017) - Sarasini, Fabrizio; Tirillò, Jacopo; Puglia, Debora; Dominici, Franco; Santulli, Carlo; Boimau, Kristom; Valente, Teodoro; Torre, Luigi
Abstract: In this work, two natural fibres extracted from fruit (borassus) and from bast (ramie) were mechanically characterized and investigated as potential natural reinforcements in biocomposites based on polycaprolactone (PCL). The PCL-based biocomposites with content of natural fibres from 10 wt% to 30 wt% were prepared via low-temperature melt-compounding. The influence of fibre content on hardness, tensile and thermal properties of the neat matrix was investigated. The results have shown that ramie fibres exhibited an overall brittle failure with fibrillation, while higher elongation at break and ductile fracture was detected for borassus fibres. Tensile behaviour and crystallinity of the neat matrix were significantly improved by introducing both fibres. In addition, the different ductility and strength of bast and fruit fibres has been exploited in hybrid formulations, confirming the possibility of tailoring the properties of the ensuing composites for a specific application.